Deformation Characteristics of Soft Marine Soil Tested under Cyclic Loading with Low Frequency - Yu Lu; Wenbin Fu; Danxuan Xue (Advances in Civil Engineering)
Soft marine soil which could be found widely at the coastal and offshore areas is usually associated with high settlement and instability, especially under cyclic loading. Many research studies have been conducted on its deformation characteristics under the cyclic loading with high frequency, whereas few works have been reported on that under the low-frequency cyclic loading which largely existed in engineering. In this work, a comprehensive series of undrained triaxial tests under cyclic loading with low frequency was conducted to investigate the deformation characteristics of soft marine soil. The results demonstrate that soil specimens accumulate plastic deformation and pore pressure under cyclic loading. Specimens tested under conditions such as high confining stress, high-stress ratio, and long cyclic period generally reveal higher deformation and pore pressure. Meanwhile, the rectangular wave presents the largest contribution to plastic strain and pore pressure, followed by the trapezoidal and triangular waves, respectively, whereas the difference between the various waves decreased gradually with the increasing load level and cyclic period. The undisturbed specimens displayed lower deformations and pore pressures than the reconstructed specimens, whereas the differences are not significant when the confining stress is much higher than the structural yield stress. Furthermore, an empirical model for predicting the evolution of pore pressure is proposed and then validated against the experimental data in both this work and the literature.